Socio-Legal Perspective of Gender Justice in Covid-19 Handling Policy in Indonesia - Yuli Sulistyawan, Aditya; Padmahantara Antonius, Eka (International Journal of Criminology and Sociology, 2022)
The COVID-19 pandemic is not only a global health emergency but also leads to a recession of the global economy on a large scale. This economic recession will certainly also affect women and men differently. In the handling of the COVID-19 pandemic, one of the policies of Indonesia’s Government was the issuance of Government Regulation 21 of 2020 on large-scale social restrictions to accelerate the handling of COVID-19. This policy raises a wide range of impacts on women in the context of women’s positions in the family and as a working woman. Thus, gender mainstreaming in the handling of COVID-19 to realize gender justice should be a special concern, especially since women have been exposed to the vulnerability of COVID-19, as well as enduring the distinctive impact of the COVID-19 handling policy regarding social roles in families and communities.